Load-velocity relationship of the deadlift exercise - Morán-Navarro, R.; Martinez-Cava, A.; Escribano-Peñas, P.; Courel-Ibanez, J. (European Journal of Sport Science, 2021)
Velocity-based training (VBT) is gaining popularity in strength and conditioning due to multiple practical advantages for auto-regulating and individualizing training volume and load on a day-to-day basis. Because the load-velocity relationship varies among exercises, the knowledge of particular equations is indispensable to effectively implement the VBT. The aim of this study was to determine the complete load- and power-velocity profile of the deadlift exercise to provide practical equations and normative values for resistance training coaches and practitioners. Twenty strength-trained men performed a progressive loading test at maximal intended velocity to determine their one-repetition maximum (1RM). Mean (MV), mean propulsive (MPV) and peak velocity (PV) were measured during the concentric phase. Both MV and MPV showed a very close relationship to %1RM (R2 = 0.971 and R2 = 0.963) with a low error of estimation (SEE = 0.08 and 0.09 m·s-1), which was maintained throughout the wide breadth of velocities. PV showed the poorest results (R2 = 0.958, SEE = 0.15 m·s-1). MV attained with the 1RM was 0.24 ± 0.03 m·s-1 and consistent between participants with different relative strengths. The load that maximized the power output was identified at ~60% 1RM. In contrast to what was observed in velocity, power outcomes showed poor predictive capacity to estimate %1RM. Hence, the use of velocity-based equations is advisable to monitor athletes` performance and adjust the training load in the deadlift exercise. This finding provides an alternative to the demanding, time-consuming and interfering 1RM tests, and allows the use of the deadlift exercise following the VBT principles.